2006
DOI: 10.1172/jci27702
|View full text |Cite
|
Sign up to set email alerts
|

TRPC6 fulfills a calcineurin signaling circuit during pathologic cardiac remodeling

Abstract: The heart responds to injury and chronic pressure overload by pathologic growth and remodeling, which frequently result in heart failure and sudden death. Calcium-dependent signaling pathways promote cardiac growth and associated changes in gene expression in response to stress. The calcium/calmodulin-dependent phosphatase calcineurin, which signals to nuclear factor of activated T cells (NFAT) transcription factors, serves as a transducer of calcium signals and is sufficient and necessary for pathologic cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

24
493
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 507 publications
(519 citation statements)
references
References 77 publications
(99 reference statements)
24
493
1
1
Order By: Relevance
“…Simple overexpression of TRPC3 or TRPC6 in the mouse heart was sufficient to induce Ca 2+ entry and enhance the cardiac hypertrophic response (4,5). Mechanistically, we and others have shown that TRPC channels engage calcineurin-NFAT signaling in the heart, a well-known prohypertrophic pathway that is both necessary and sufficient for growth (4)(5)(6)(7). Indeed, deletion of calcineurin Aβ reduced hypertrophic inducibility by TRPC3 overexpression in the heart (5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Simple overexpression of TRPC3 or TRPC6 in the mouse heart was sufficient to induce Ca 2+ entry and enhance the cardiac hypertrophic response (4,5). Mechanistically, we and others have shown that TRPC channels engage calcineurin-NFAT signaling in the heart, a well-known prohypertrophic pathway that is both necessary and sufficient for growth (4)(5)(6)(7). Indeed, deletion of calcineurin Aβ reduced hypertrophic inducibility by TRPC3 overexpression in the heart (5).…”
Section: Discussionmentioning
confidence: 99%
“…More provocatively, TRPC channels probably coexist with TRPM and TRPP subclasses of channels in even larger channel complexes (16,17). Because all TRPC family members have been detected in the heart, some of which are up-regulated by hypertrophy (4)(5)(6)(7)23), it is likely that many combinations of tetramers are possible and can generate unique cation influx properties. However, combined inhibition of both subfamilies in dnTRPC4, dnTRPC3 DTG mice completely eliminated all TAC-associated Ca 2+ entry, suggesting that not all TRPC complexes show crossoligomerization in the heart.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several recent studies have provided evidence that TRPCs may also be functional in the heart (18,28,30). Ohba et al (30) demonstrated that hypertrophic stimuli increased TRPC1 expression both in the intact heart and in isolated cardiomyocytes (30).…”
mentioning
confidence: 99%
“…-254C>G localizes within the promoter region of the TRPC6 gene, which contains several transcription binding sites, such as nuclear factor of activated T cells (19,20). In cardiomyocytes, TRPC6 was upregulated through the calcineurin-nuclear factor of activated T cells signaling pathway leading to cardiac Articles Kuang et al…”
Section: Discussionmentioning
confidence: 99%